Kinerja Komisi Pemilihan Umum Kota Bitung Dalam Pemilu Presiden Dan Wakil Presiden Tahun 2014 - Bilote, Donly; Liando, Daud; Mamentu, Michael (JURNAL ILMIAH SOCIETY, 2016)
A lot of appreciations had been founded in 2014 president and vice-president election by the work of the general election committee in bitung city. However, inadequacy at the moment marked over the professional aspect and the way the election held with. The purpose of this research was then to analyze and identify the work of the general election committee correctly. This research took place at the general election committee at Bitung city with using qualitative design through data reduction, display data and verification technique. Interview, observation, as well as documentation were used to collect the data. Meanwhile, the instrument in this research was the researcher himself in order to support the data. This study uses a theoretical approach of KumorotomoÂ  is about the efficiency, effectiveness, fairness and responsiveness. Drawing on the results of this analysis, this research outlined that the work which had been done by the general election committee were not suitable due to languid regulation, human resource allocation, participation and consideration of the local people. Keywords : Performance, President and vice-President Election.